Supercritical fluid extraction (SFE) of Malaysian wild ginger Zingiber puberulum inflorescence - Omar, Muhammad Nor; Razman, Summaiya; Muhd Nor, Nor Nazuha; M N, Muhammad Nazreen; Zuberdi, Ahmad Muzammil (Oriental Scientific Publishing Co., 2013)
Study on bioactive compounds in essential oil of Malaysian wild ginger species, Zingiber puberulum was carried out. The essential oil was extracted from the inflorescence of Z. puberulum using SFE at 48 Mpa and 40°C of extracting pressure and temperature respectively. The oil was then analysed using gas chromatography-mass spectrometry (GC-MS) instrument. Twenty-one compounds were found in the SFE extract of Z. puberulum with fatty acids; i.e. palmitic acid (65.7%) and oleic acid (15.9%) were the major constituents and small percentages of various terpenic compounds. The sesquiterpene compounds identified in the SFE extract of Z. puberulum were α-bisabolol, β-elemene and caryophyllene. It was found that SFE could be used successfully to extract a wide variety of important bioactive compounds in Z. puberulum but that the conditions may need to be optimized to ensure the optimum yield of the volatile compounds.